Efektivitas Ekstrak Etanol Biji Anggur Merah (Vitis vinifera) terhadap Jumlah Fibroblas pada Perawatan Ortodonti - Herawati, Hillda; El Fithriyah, Rhabiah; Ruswandi, Ahda A. Q. (e-GiGi, 2025)
Abstract: Malocclusion can be solved with orthodontic treatment. In orthodontic treatment, there will be movements motivated by inflammatory responses and tissue responses in the form of resorption and apposition or bone remodeling. Some of the cells responsible for the process are fibroblasts, osteoblasts, and osteoclasts. Grape seeds contain many active compounds that have high levels of antioxidants and phytoestrogens that can increase the division and proliferation of fibroblasts. This study aimed to find out whether grape seed ethanol extract was effective in increasing fibroblast cell count in orthodontic treatment. This was an experimental laboratory study conducted by attaching an elastomer separator and giving 4% ethanol extract of red grape seeds 0.2 ml in seven groups of guinea pigs that met the inclusion criteria and then were evaluated on days 1, 7, and 14. The Anova test showed a p value of < 0.001 (p<0.05) which meant that there was a statistically significant difference between the treatment groups and the test groups on days 7 and 14. The number of fibroblasts increased from day 1, 7 to day 14. The lowest number of fibroblasts was obtained in the control group (11.7±0.70) while the highest number of fibroblasts was found in the guinea pig group applied rubber separator and given 4% red grape seed extract as much as 0.2ml for 14 days (21.75±1.29). In conclusion, grape seed extract is effective in increasing the number of fibroblasts in orthodontic treatment and is most effective on day 14. Keywords: grape seed; fibroblasts; malocclusion; orthodontic treatment    Abstrak: Masalah maloklusi dapat diselesaikan dengan melakukan perawatan ortodonti. Pada perawatan ortodonti akan terjadi pergerakan yang dilatarbelakangi oleh respon inflamasi dan respon jaringan berupa resorpsi dan aposisi atau remodeling tulang. Beberapa jenis sel yang bertanggung jawab atas proses tersebut ialah fibroblas, osteoblas, dan osteoklas. Biji anggur mengandung banyak senyawa aktif yang memiliki tingkat antioksidan tinggi dan fitoestrogen yang mampu membantu meningkatkan pembelahan serta proliferasi dari fibroblas. Penelitian ini bertujuan untuk mengetahui apakah ekstrak etanol biji anggur efektif dalam meningkatkan jumlah sel fibroblas pada perawatan ortodonti. Jenis penelitian ialah eksperimental laboratoris dengan memasangkan separator elastomer dan memberikan ekstrak etanol biji anggur merah 4%  sebanyak 0,2 ml pada tujuh kelompok marmut sesuai kriteria inklusi dan dievaluasi pada hari ke-1, hari ke-7, dan hari ke-14. Uji Anova menunjukkan nilai p <0,001 (p<0,05) yang berarti terdapat perbedaan bermakna antara kelompok perlakuan dan kelompok uji dihari ke-7 dan ke-14. Jumlah fibroblas meningkat dari hari ke-1, ke-7 sampai hari ke-14. Jumlah fibroblas paling rendah didapatkan pada kelompok kontrol (11,7±0,70) sedangkan jumlah fibroblas yang paling meningkat terdapat pada kelompok marmut yang diaplikasikan karet separator dan diberi 4% ekstrak biji anggur merah sebanyak 0,2 ml selama 14 hari (21,75±1,29). Simpulan penelitian ini ialah ekstrak biji anggur efektif dalam meningkatkan jumlah fibroblas dalam perawatan ortodonti, paling efektif pada hari ke-14. Kata kunci: biji anggur; fibroblas; malokusi; perawatan ortodonti